Pendampingan Manajemen Kualitas Produksi Tas di PT TIJ - Anik Nur Habyba; Triwulandari Satitidjati Dewayana; Indah Permata Sari; Idriwal Mayusda; Ahmad Farhan; Iveline Anne Marie (Abdimas Universal, 2023)
PT TIJ is a company that produces the local brand "LC," which is located in Depok, West Java. According to data for June-August 2022, there are significant product returns of around 1-7%, and a repair process is needed during production. Quality control at PT TIJ is carried out by checking goods one by one by supervisors and production operators. Recording quality problems is only done by labeling the products that need repair. The Quality Assurance (QA) department only records the number of products that need repair. Documentation of specific defects that often occur has never been done. Documentation is one of the essential things for quality control because quality data plays a significant role in making process improvement decisions. This PkM program is carried out by providing training materials for implementing an integrated system of sustainable quality management and the importance of quality data providing information related to problems in the production process. The conducted training increased the participants' knowledge regarding management and quality data. The usefulness of the training was confirmed directly to the participants through a questionnaire. The results showed that 77% of participants strongly agreed that the material was helpful, and 73% strongly agreed that the presenter delivered the quality management material well. Participants also provided suggestions regarding material for further assistance related to using a computer to use quality data analysis tools.